A Study on Sensor Networks and its Research in Recent Application Developments - Immanuvel Arokia James, K; Prabu, R; Mary Judith, A; Gladis Flower, L (International Journal of Engineering and Technology, 2018)
In recent days Wireless Sensor Networks and Internet of Things have become a growing and challenging research area. Those are used in various hard and sophisticated real time environments. A lot of challenges have to be faced by the researchers in these areas to meet the features like the quality level of sensed data, nodes autonomy, less energy utilization, battery storage, cluster range with cluster head selection and size of nodesâ€¦etc. In this paper, We did an extensive analysis on their recent developments in various application areas such as intelligent buildings, smart homes, Smart city developments, healthcare and smart hospital, transport and traffic management, Horticulture, water resources and quality monitoring, smart grid, space researchâ€¦etc. This analysis will be helpful for the fresh researchers for doing research in WSN and IoT. The researchers have to look in identifying better solutions to the above said challenges must meet.Â